Food aid reduces poverty. - World Food Programme, Bangladesh ([Dhaka : World Food Programme, Bangladesh, 1997)
With reference to Bangladesh.
Includes bibliographical references (p. 29).
Includes statistical tables.
Keywords: World Food Programme; Food relief -- Bangladesh; Poverty -- Bangladesh